Strategies for Enhancing Information System and Internet Security Towards Adware Threats - Shelvia Nur Widiastuti; Anisa Indriani; Ucu Nugraha (LP2M Universitas Widyatama, 2023)
Adware has emerged as a significant concern in today's information systems and internet security landscape. This malicious software type illicitly injects unwanted advertisements into user devices, disrupting user experience and posing threats to privacy and data security. Effective strategies are essential to mitigate adware threats and enhance information systems and internet security.This article explores several strategies to combat adware threats. Firstly, adopting a preventive approach is crucial. Utilizing reliable and regularly updated security software, alongside frequent updates of operating systems and applications, can effectively prevent adware infections. Secondly, avoiding clicking on suspicious links and pop-ups can minimize the risk of adware infiltration. Thirdly, regular clearing of cookies and caches aids in purging adware from user devices. Lastly, employing ad blockers serves as an additional measure to thwart adware presence on user devices. By implementing these strategies, organizations, and individuals can significantly reduce their vulnerability to adware attacks, thereby safeguarding both user experience and data integrity in the evolving landscape of information technology and internet usage.